Teacher training in Mathematics Fairs: an opportunity to reflect on the advising process - Schroeder, Tiago Ravel; Oliveira, Fátima Peres Zago de; Henning, Elisa (Revista Internacional de Pesquisa em Educação Matemática, 2023)
Throughout the development of the educational product linked to Schroeder (2021), it was possible to move between the three pedagogical moments. In them, the different facets of the Network Movement of the Mathematics were discussed, however, the focus was on the advising process and its contributions to the training of teachers. At the end, interviews were carried out with the participants. The questions are organized into four blocks. Later, the responses were subjected to a Discursive Textual Analysis (DTA), which allowed to identify contributions before, during and after participating in the event. Regarding the experiences before, the epistemological conceptions of the advisers were evidenced. At the time of the event, pedagogical contributions were perceived for the work in the classroom. After the event, contributions related to the registration of activities and evaluation of the work for the following years were perceived.